The Driller Killer - Ferrara, Abel; Kelsch, Ken; Marz, Carolyn; Day, Baybi (ILC Entertainment, 2007)
In the 1970s the shock horror genre achieved popularity with the directorial debut of Wes Craven's "The Last House On The Left", Tobe Hooper's "The Texas Chainsaw Massacre" and Abel Ferrara's "Driller Killer". "Driller Killer" tells the story of an aspiring artist (played by Ferrara under his 'stage' name Jimi Laine) who is driven mad by his struggles and the pressures of urban life. Armed with a hand-drill and a taste for murder he takes to the streets in a bloody rampage. This film takes the viewer on a shocking realistic journey into madness and murder. It leaves you questioning your own sanity and that of those around you. "Driller Killer" was the first film in the infamous and often controversial career of Abel Ferrara. It combines the veneful horror of his second film "MS.45" with the edgy and violent characters he created in "Bad Lieutenant", "The Funeral" and "King Of New York". [Cover]
Keywords: DVD-Video